Beyond implementation: Uncovering the parallels between de-implementation and antimicrobial stewardship. Issue 1 (17th April 2023) - Advani, Sonali D.; McKay, Virginia
Abstract: De-implementation is defined as the process of discontinuing, removing, reducing, or replacing a harmful, ineffective, or low-value clinical practice or intervention. The goal of de-implementation strategies is to minimize patient harm, maximize use of resources, and reduce healthcare costs and inequities. Both antibiotic and diagnostic stewardship programs focus on reducing low-value interventions (tests or antimicrobials). Stewardship interventions commonly involve de-implementation and deprescribing strategies. This commentary explores unique aspects of deimplementing low-value testing and unnecessary antimicrobial use, similarities between de-implementation and stewardship approaches, multilevel factors that impact de-implementation, and opportunities for future research.